Clinical Course of Atopic Dermatitis in an Adult with Amyotrophic Lateral Sclerosis: Aetiological Implications of Voluntary Movements and Dermatitis Severity - Tatsushi Kiyohara; Takayasu Fukudome; Yoshiyuki Kamio; Yuta Koike; Hiroyuki Murota (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)